THE ARTIFICIAL INTELLIGENCE REVOLUTION AND ITS ROLE IN TEACHING LANGUAGES - Isomova Nozimabonu Baxtiyor qizi (Modern American Journals, 2025)
This article explores the transformative impact of the Artificial Intelligence (AI) revolution on language education. It examines how AI-powered tools-such as intelligent tutoring systems, speech recognition, machine translation, and personalized learning platforms-are reshaping traditional approaches to language teaching and learning. The article highlights the benefits of AI, including increased accessibility, adaptive learning experiences, and real-time feedback, while also addressing potential challenges such as data privacy, teacher displacement, and the need for ethical frameworks. The study concludes that AI, when thoughtfully integrated, can enhance language acquisition and support both learners and educators in achieving more effective and engaging outcomes.The findings suggest that AI is reshaping the landscape of language education by promoting personalization, accessibility, and efficiency, while also posing challenges related to ethics, data privacy, and pedagogical integration.
Keywords: Artificial Intelligence, Language Learning, Education Technology, NLP, Intelligent Tutoring Systems, EdTech, speech recognition